Serbia Financial Sector Assessment Program Update : Crisis Management Framework - International Monetary Fund; World Bank (Washington, DC, 2017)
In light of the outflow of deposits in Serbia in late 2008 and early 2009, a series of measures were introduced to urgently address stability concerns. These measures included increased deposit insurance coverage, shortened payout periods, introduction of regulations on lenders of last report (LoLR) and new liquidity lines, and the possibility for the Deposit Insurance Agency (DIA) to purchase shares of insolvent banks under instruction from the Government of Serbia (GoS). At the time, it was understood that, once stability returned, it will be prudent to have a crisis management framework in place to address systemic financial crises at all times, much like some countries have a framework to deal with natural disasters. The new framework will seek to minimize the need for ad hoc measures during crises and limit the need for the authorities to take measures that are technically illegal. Because of the lack of such crisis provisions, in several past crises, ministers and governors were forced by deteriorating events to take measures for which they had no authority, leaving the passage of appropriate regulation or laws to the aftermath of the crisis. This technical note has been prepared in the context of the initiative, primarily spearheaded by the National Bank of Serbia (NBS), to develop a contingency management framework. In particular, the note discusses the key elements of such a framework, explores how the NBS and other countries are tackling such contingency planning.